Effectiveness of the World Health Organization Safe Childbirth Checklist (WHO-SCC) in preventing poor childbirth outcomes: a study protocol for a matched-pair cluster randomized control trial - Tieba Millogo; Kadidiatou Raïssa Kourouma; Aïssatou Diallo; Marie Laurette Agbre-Yace; Mamadou Diouldé Baldé; Seni Kouanda (BMC, 2021)
Abstract Background Women delivering in health facilities in sub-Saharan Africa and their newborns do not always receive proven interventions needed to prevent and/or adequately manage severe complications. The gaps in quality of care are increasingly pointed out as major contributing factor to the high and slow declining perinatal mortality rates. The World Health Organization Safe Childbirth Checklist (WHO-SCC), as a quality improvement strategy, targets low cost and easy to perform interventions and suits well with the context of limited resource settings. In this matched-pair cluster randomized controlled trial, we assess the effectiveness of the WHO-SCC in improving healthcare providers' adherence to best practices and ultimately improving childbirth outcomes. Methods This is a multi-country study. In each country we will carry out a matched-pair cluster randomized controlled trial whereby four pairs of regional hospitals will be randomized on a 1:1 basis to either the intervention or control group. A context specific WHO-SCC will be implemented in the intervention facilities along with trainings of healthcare providers on best childbirth practices and ongoing supportive supervisions. The standard of care will prevail in the control group. The primary outcome is a summary composite metric that combine the following poor childbirth outcomes: stillbirths, maternal deaths, early neonatal deaths, severe postpartum hemorrhage, maternal infections, early neonatal infections, prolonged obstructed labor, severe pre-eclampsia, uterine rupture in the health facility, eclampsia and maternal near miss. The occurrence of these outcomes will be ascertained in a sample of 2530 childbirth events in each country using data extraction. A secondary outcome of interest is the adherence of healthcare providers to evidence best practices. This will be measured through direct observations of a sample of 620 childbirth events in each country. Discussion Our study has the potential to provide strong evidence on the effectiveness of the WHO-SCC, a low cost and easy to implement intervention that can be easily scaled up if found effective. Trial registration The trial was registered in the Pan-African Clinical Trials Registry on 21st January 2020 under the following number: PACTR202001484669907. https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=9662